The interface between clinical and performance related biomechanics - An emerging researcher`s journey - Strutzenberger, G (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The presentation will describe the journey my career has taken so far, using three main themes, which have been selected to reflect my experience to date. The examples demonstrate how sports biomechanics can contribute towards developing new knowledge in a multidisciplinary setting with specific reference to the interface between clinical practice and performance related biomechanics. The three main themes will include: Clinical Biomechanics (ACL injury), Adapted Performance (Amputee Sprinting), and Environmental Interaction (Artificial Turf). The initial theme Clinical Biomechanics, emerges from my work at the University of Salzburg, exploring ACL-injury and a conservative treatment (RegentK), where acute effects of ACL-injury on gait and lower limb impacts will be discussed. The second theme will examine the contemporary aspect of Adapted Performance, specifically the use of blades in amputee sprinting during the sprint start; this example draws on a successful collaboration with the German Sports University Cologne, Germany and the Cardiff School of Sport, Cardiff Met, UK. The final theme, Environmental Interaction, investigates the use of artificial turf in soccer and rugby. I will discuss my work as a Research Officer on the FIFA, IRB, and Cardiff School of Sport project. This research employed an interdisciplinary approach to address the question of perception (psychology) and performance (biomechanics) on the introduction of artificial turf. Finally, I will draw some global conclusions regarding my research experience to date and will present perspectives for the future.